On Sustainable Consumption: The Implications of Trade in Virtual Water for the EU’s Food Security - Alina Petronela Alexoaei (MDPI AG, 2021)
The paper addresses the sustainability of the European Union’s food consumption through a water footprint assessment of selected vulnerable agricultural imports from a two-pronged perspective: (1) the degree of the EU’s dependence on global green water resources embedded in the apparent consumption of selected water-intensive agricultural products and (2) the degree of commitment of countries of origin to sustainability policies. The study argues that the vulnerability of the EU’s agricultural imports to water risks can be estimated based on the amount of green water consumed in producing crops in the countries of origin. The results show that the EU’s consumption of agricultural goods is highly dependent on virtual water imports for all six selected vulnerable agricultural products, from the lowest footprint for bananas (5 mil. km3) to the largest for coffee (69 mil. km3). The analysis also points to a greater concern for quality issues in the countries of origin (56.53%) relative to management (26.52%) and availability issues (16.85%), but the latter are to arise in importance for sustainable production in the years to come. Our conclusions contribute to building up a responsible commitment towards (1) development of environmental policies and the design of practical measures by providing quantitative information that makes problems more clearly defined and tangible, and (2) assessing the outcome of policies and practical measures by understanding their effects on the sustainability of food consumption.